Optimal Information Disclosure and Collusion - Andreas Asseyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies optimal information disclosure under the threat of collusion. A principal seeks to procure a good from one of two agents who can collude against the principal. The first agent has a publicly known cost of production and the second agent's cost is his private information. The principal decides how much information the first agent receives about the costs of the second agent. In the choice of the optimal disclosure policy, the principal faces a trade-off: More information disclosure makes the elicitation of private in- formation easier but facilitates collusion at the same time. It is optimal for the principal to partially disclose information. Under the optimal information structure, none of the agents receives a positive information rent.
Keywords: D82; D83; D86; 330